Effects of Nitrite Stress on Growth, Glycolipid Metabolism, and Hepatic Metabolome in Spotted Seabass (Lateolabrax maculatus) Under High-Temperature Conditions - Juan Gao; Shi Cao; Chen Shen; Jian Zhang; Ling Wang; Xueshan Li; Kangle Lu; Chunxiao Zhang; Kai Song (Animals)
Nitrite is a common pollutant in aquaculture systems and can pose serious threats to fish health, especially under high-temperature conditions. This study aimed to investigate the impact of nitrite stress on the growth, glycolipid metabolism, and hepatic metabolomic profiles in the spotted seabass fry (Lateolabrax maculatus) under elevated temperature conditions at 33 °C. A total of 450 fish (28.52 ± 0.84 g) were randomly distributed into nine tanks and exposed to three nitrite concentrations (0, 8, and 16 mg/L), with samples collected on days 1, 3, 7, 14, 21, and 28. Results showed that higher nitrite levels significantly reduced final body weight, weight gain, survival rate, hepatosomatic index, and viscerosomatic index. Blood glucose and triglyceride levels, whole-body crude lipid, liver total cholesterol, and hepatic glycogen content also declined significantly under higher nitrite stress. In contrast, hepatic lactate and lactate dehydrogenase increased in the high-nitrite group. Gene expression analysis revealed suppressed lipid synthesis and enhanced lipolysis under nitrite exposure. Metabolomic analysis further demonstrated disruptions in key energy-related pathways, including the TCA cycle, pentose phosphate pathway, and insulin signaling. These findings indicate that nitrite stress impairs growth and energy metabolism in spotted seabass, which respond by mobilizing energy reserves to cope with combined stress of high temperature and nitrite.